1992
DOI: 10.1093/nar/20.18.4919
|View full text |Cite
|
Sign up to set email alerts
|

A novel POU homeodomain gene specifically expressed in cells of the developing mammalian nervous system

Abstract: We report the isolation of a novel human POU domain encoding gene named RDC-1. The POU domain of the RDC-1 encoded protein is highly related to the POU domain potentially encoded by the rat brain-3 sequence and to that of the Drosophila I-POU protein; outside of the POU region, RDC-1 is unrelated to any previously characterized protein. The RDC-1 gene is expressed almost exclusively in normal tissues and transformed cells of neural origin. In the developing mouse and human fetus, RDC-1 is expressed in a spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 24 publications
4
42
1
Order By: Relevance
“…Expression in neural progenitor/NB hybrid ND7 cells is likely to derive from their progenitor component. Results previously describing BRN3A transcript expression in approximately 70% of EFT and derived cell lines but not in NB samples (Collum et al, 1992) correlate well with our findings.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Expression in neural progenitor/NB hybrid ND7 cells is likely to derive from their progenitor component. Results previously describing BRN3A transcript expression in approximately 70% of EFT and derived cell lines but not in NB samples (Collum et al, 1992) correlate well with our findings.…”
Section: Resultssupporting
confidence: 92%
“…BRN3A has been proposed to have an intact oncogenic function in EFT (Collum et al, 1992;Theil et al, 1993), and a potential positive correlation of BRN3A distribution in primary EFT samples with invasion (Table 1) (negative control) and GLI-1 (positive control) fragments in SKNMC cells using whole rabbit IgG or specific a-FLI-1 antibodies and amplification oligonucleotides as described in the Materials and methods section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of high levels of Brn-3a have previously been found in cervical, NE cancers and Ewing's sarcoma. [11][12][13] However, Brn-3a expression has only been compared to levels in corresponding noncancer tissue in cervical cancer, and found Brn-3 transcription factors in prostate cancer JKJ Diss et al to be upregulated. 11 Similar to the present study, overexpression of Brn-3a was found to increase cervical cancer cell growth in vitro and tumour growth in vivo.…”
Section: Upregulation Of Brn-3a[s] In Cap and Role In Growthmentioning
confidence: 99%
“…4,10 Expression of these transcription factors has also been found to be altered in a number of different cancers in vitro and in vivo. Thus, Brn-3a levels are significantly elevated (mRNA, B300-fold; protein, B6-fold) in cervical cancers 11 and are also high in aggressive NE tumours including small-cell lung carcinomas, 12 Ewing's sarcoma and neuroepitheliomas; 13 Brn-3b is expressed at high levels in neuroblastoma 14,15 and teratocarcinoma cells 15 and its expression is upregulated in a subset of malignant breast cancers; 16 Brn-3c expression is reduced in small-cell (Merkel cell) carcinomas of the skin with poor prognosis. 17,18 Brn-3a, Brn-3b and Brn-3c genes share a common structure, composed of two exons separated by a short intronic sequence.…”
Section: Introductionmentioning
confidence: 99%